Inclusive Leadership and Taking-Charge Behavior: Roles of Psychological Safety and Thriving at Work - Zeng, Hao; Zhao, Lijing; Zhao, Yixuan (Frontiers in Psychology, 2020)
Taking charge is an important form of proactive behavior that sustains organizational survival and individual development. Learning how to motivate employees to engage in taking charge behavior has become among the hot topics in the field of organizational management. Despite considerable research investigating the factors influencing taking charge, less attention has been paid to leadership-related factors, such as inclusive leadership. Based on self-determination theory and social information processing theory, we examined the mediating roles of psychological safety and thriving at work in the relationship between inclusive leadership and taking charge behavior. We collected data in two stages from 205 pairs of employees and their supervisors at 17 companies in mainland China. Specifically, the results revealed that inclusive leadership promoted employees’ taking charge behavior first through psychological safety and then thriving at work. The results describe a more detailed mechanism underlying the formation of taking charge behavior. The results further deepen our understanding of the path from inclusive leadership to employee behavior. These findings have theoretical implications for the taking charge literature and managerial implications for practitioners.